Identification of opioid use disorder using electronic health records: Beyond diagnostic codes - Poulsen, Melissa N.; Nordberg, Cara M.; Troiani, Vanessa; Berrettini, Wade; Asdell, Patrick B.; Schwartz, Brian S. (Drug and alcohol dependence, 2023)
We used structured and unstructured electronic health record (EHR) data to develop and validate an approach to identify moderate/severe opioid use disorder (OUD) that includes individuals without prescription opioid use or chronic pain, an underrepresented population. Using electronic diagnosis grouper text from EHRs of ~1 million patients (2012–2020), we created indicators of OUD—with “tiers” indicating OUD likelihood—combined with OUD medication (MOUD) orders. We developed six sub-algorithms with varying criteria (multiple vs single MOUD orders, multiple vs single tier 1 indicators, tier 2 indicators, tier 3 and 4 indicators). Positive predictive values (PPVs) were calculated based on chart review to determine OUD status and severity. We compared demographic and clinical characteristics of cases identified by the sub-algorithms. In total, 14,852 patients met criteria for one of the sub-algorithms. Five sub-algorithms had PPVs ≥0.90 for any severity OUD; four had PPVs ≥0.90 for moderate/severe OUD. Demographic and clinical characteristics differed substantially between groups. Of identified OUD cases, 31.3% had no past opioid analgesic orders, 79.7% lacked evidence of chronic prescription opioid use, and 43.5% lacked a chronic pain diagnosis. Incorporating unstructured data with MOUD orders yielded an approach that adequately identified moderate/severe OUD, identified unique demographic and clinical sub-groups, and included individuals without prescription opioid use or chronic pain, whose OUD may stem from illicit opioids. Findings show that incorporating unstructured data strengthens EHR algorithms for identifying OUD and suggests approaches limited to populations with prescription opioid use or chronic pain exclude many individuals with OUD. •Electronic health records (EHRs) facilitate opioid use disorder (OUD) research.•EHR OUD studies often have a limited focus on chronic pain and prescription opioids.•Approaches are needed to identify OUD from EHRs that do not rely only on diagnoses.•We developed and validated a method to identify OUD using multiple data elements.•Our method included a population with illicit opioid use and lacking OUD diagnoses..